Tafsir al Qurtubi al Jami'li Ahkam al Qur'an - Abi Abdullah Muhammad Ibn Ahmad al Ansariy al Qurtubiy (Dar al Shu'ub)
ws.jl.1,4,.c.1, jl.2,3,5,6-8.c.1-2/stoc6; jl.1=c.1; jl.2-3=c.1-2; jl.4=c.1; jl.5-8=c.1-2